Ashton Applewhite in Conversation with Anita Wohlmann - Wohlmann, Anita; Applewhite, Ashton (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
This interview is part of the forum “Too old for the job? The 2024 US American Presidential Elections." It was recorded on April 10, 2024, transcribed with otter.ai, and edited for clarity by Ashton Applewhite. An audio version is available here.